El monopolio en el servicio público de suministro de agua en España: conflictos y tutela - Villar Rojas, Francisco José (2016)
In Spain, the monopoly provision of potable water supply struggles with means to obtain that resource from other sources. The viability of the public service requires mechanisms of protection against such supplies. This study analyzes the foundation and meaning of the declaration of monopoly; legal exceptions to that regime, particularly self-consumption cases; and mechanisms to protect public service provision and, if necessary, restore the monopoly and its balances.